Quantitative analysis of voluntary movement and anticipatory postural adjustments: a functional approach. Issue 15 (18th November 2021) - Amici, Cinzia; Ragni, Federica; Piovanelli, Barbara; Buraschi, Riccardo; Faglia, Rodolfo; Negrini, Stefano; Pollet, Joel
Abstract: Daily living activities and tasks like standing forward reaching present complex Anticipatory Postural Adjustments (APAs), and an objective, repeatable, subject- and task-dependent procedure to detect Voluntary Movements (VM) and APAs onsets is still missing. This paper proposes a new approach to the VMs study, based on a functional mechanical interpretation of the movement performing, which allows defining kinematic and dynamic APAs. A protocol for the identification of VMs and APAs onsets in the reaching movement is presented. Acquired data on 9 healthy young subjects enable a preliminary validation of this method suitability as support for an objective quantification of APAs.